Bleomycin and Olaparib Induced Modulation of Poly (ADP-Ribose) Polymerase 1 Activity and Chromatin Structure in Thymocyte Nuclei - Asatryan, Anush L. (Asian Journal of Pharmaceutics (AJP), 2023)
Objective: Poly (ADP-ribose) polymerase 1 inhibitors (PARPi) are used in the treatment of cancer patients as monotherapy agents or in combination with approved anticancer drugs to optimize their clinical use. However, the development of novel anticancer chemotherapy is tempered by the potential detrimental side effects displayed by cytotoxic drugs in healthy cells. To delineate the rationality of PARPi olaparib (OLA) in combination with the approved DNA-damaging anticancer drug bleomycin (BLM), we investigated the influence of the drugs on poly (ADP-ribose) polymerase 1 (PARP 1) activity, chromatin, and DNA structure in healthy rat thymocyte nuclei. Materials and Methods: Wistar albino male rats (Rattus norvegicus, 6 weeks old) were used throughout the experiments. Animals were obtained from the stock of the animal house of the faculty of biology at YSU. The enzymatic assay for PARP 1 activity was performed according to the original method based on the estimation of residual NAD+ concentration in the PARP assay mix adapted by us to quantify NAD+ consumed by isolated nuclei. DNA concentrations were measured by the spectrophotometric method using an extinction coefficient ε260=6600 M-1 cm-1. Statistical differences in results between groups were evaluated by the Student’s t-test. P < 0.05 was considered significant. Key Results: It was observed that in healthy rat thymocyte nuclei, BLM induced PARP-1 inhibition and DNA and chromatin loosening. In contrast, treatment with OLA maintained chromatin and DNA condensation, which could partly underlie the cytotoxic effect of OLA as a result of drug-induced downregulation of chromatin-associated nuclear functions. Our findings provide evidence for the revalidation of the rationality of OLA application in combination chemotherapy regimens involving BLM.